TRANSFORMATION TENDENCIES OF HIGHER EDUCATION IN MODERN SOCIO-ECONOMIC CONDITIONS - Кравчук , Галина; Шевчук , Тетяна (Socio-economic relations in the digital society, 2020)
The article analyzes the current state of development of information technologies, in particular, information intelligent systems that directly affect the transformation of methods and forms of education. Prospects for the development of intelligent information systems in student education are due to the interaction of several branches of knowledge — technical, pedagogical, psychological, which allows us to conclude about the interdisciplinary nature of the development of intelligent learning systems and education in general. As a result of continuous long-term improvement of the technological process of manufacturing integrated circuits and processors, a platform of the future intellectual society is formed, which will be based on NBIC-technologies (convergence of nano-, bio-, information, cognitive technologies), cloud computing and mobile applications. Improving methods of searching for educational information; high popularity of webinar-oriented platforms; use of three-dimensional graphics and principles of game mechanics for online conferences, lectures, seminars, trainings, educational games; educational opportunities of social networks involve the formation of new forms of learning. Open learning via the Internet will become a traditional form of education. Mobile devices will be considered as the main tools for organizing training. Paper editions will be replaced by electronic multimedia content. Multi-user virtual 3D worlds will replace physical visits to higher education institutions. Open educational resources will be widely used by all subjects of the educational process. Virtual mobility will break down barriers between national education systems. The authors emphasize the problem of legislative regulation of the use of «formal», «non-formal» and «informal» education and their  integration in the educational process of higher education institutions.
Keywords: educational systems; information technologies; forms of education; information intelligent systems; virtual mobility; network learning; mass open online courses; webinar